2006
DOI: 10.1200/jco.2005.04.5963
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and Temozolomide for Newly Diagnosed Glioblastoma: Recursive Partitioning Analysis of the EORTC 26981/22981-NCIC CE3 Phase III Randomized Trial

Abstract: RPA retains its prognostic significance overall as well as in patients receiving RT with or without TMZ for newly diagnosed GBM, particularly in classes III and IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
294
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 450 publications
(314 citation statements)
references
References 25 publications
(23 reference statements)
8
294
1
11
Order By: Relevance
“…Patients with lowgrade astrocytoma have a survival average of 7 -10 years in contrast to our population, which showed a survival median of 3.4 years. In the same manner, patients with high-grade astrocytomas, treated with chemotherapy and concomitant radiotherapy and posteriorly with adjuvant temozolamide, have a median survival of 12.1 -14.6 months (Mirimanoff et al, 2006), in contrast to the patients in our study who displayed a median survival of 7 months. These disparities could be accounted for by: (1) the nature of the studies (observational vs controlled studies), and (2) differences in the treatment schema.…”
Section: Discussionsupporting
confidence: 54%
“…Patients with lowgrade astrocytoma have a survival average of 7 -10 years in contrast to our population, which showed a survival median of 3.4 years. In the same manner, patients with high-grade astrocytomas, treated with chemotherapy and concomitant radiotherapy and posteriorly with adjuvant temozolamide, have a median survival of 12.1 -14.6 months (Mirimanoff et al, 2006), in contrast to the patients in our study who displayed a median survival of 7 months. These disparities could be accounted for by: (1) the nature of the studies (observational vs controlled studies), and (2) differences in the treatment schema.…”
Section: Discussionsupporting
confidence: 54%
“…Randomization was performed centrally with the use of an interactive voice-response system, with stratification according to study region (Western Europe, Eastern Europe, Asia, United States, or other) and recursive partitioning analysis class (III, IV, or V). 23 (There are six recursive partitioning analysis classes, of which classes III, IV, V, and VI are used to categorize glioblastoma, with higher numbers representing a worse prognosis. Class VI patients were considered too frail to participate in this study.…”
Section: Randomization and Treatmentmentioning
confidence: 99%
“…Recent trials in newly diagnosed GBM patients have shown that addition of temozolomide concomitant with radiotherapy increased median survival to 14.6 months [39], the first meaningful increase in survival in this patient population in about 25 years. Even with this advance, there is an obvious need for further advances in brain tumor treatment, particularly because most classes of patients do not receive a significant increase in survival with the addition of temozolomide [40]. Furthermore, if the effect of temozolomide in combination with a targeted radionuclide agent is the same as observed with external beam radiation, then investigation of 211 At-labeled chimeric 81C6 plus temozolomide should be considered.…”
Section: Potential Impact On Clinical Outcomementioning
confidence: 99%